Nilai Religiusitas dalam Film Laskar Pelangi Karya Andrea Hirata - Annisa, Anis Nur; Sakinah, Myrna Nur (Jurnal Artikula, 2020)
The purpose of this research is to interpret the values ​​of religiosity in the film Laskar Pelangi by Andrea Hirata. The study uses a semiotic research method. This method is used to describe the contents expressed or implied in the film. The findings of the research on the value of religiosity in the film Laskar Pelangi are in essence an author's attempt to help the reader realize his values. The value of religiosity includes human personal life in relation to God. These values ​​are contained in dialogues and images. The dialogue presented in the film, partly comes from the teachings of Islam. The film also depicts scenes of exemplary figures and worship practices. The film Laskar Pelangi provides a moral message that encourages viewers to change into better personalities and noble morals. The results of the study are expected to be an input for the public to be able to use film as a means to take positive messages in self improvement and the surrounding environment.